LINGKUNGAN HIDUP STRATEGIS TERHADAP PERENCANAAN TATA RUANG KABUPATEN BOLAANG MONGONDOW TAHUN 2011-2030 - Lepa, Alex A.; Polii, Bobby J.V.; Husain, Jailani (EUGENIA, 2011)
ABSTRACT   Strategic Environmental Assessment (SEA) can be done to ensure that the preparation of policy, planning and program (PPP)  on  spatial plan draft  of Bolaang Mongondow Regency  have included the sustainable development. The purpose of this study was (1) to asses whether the PPP have included the linkage, balance, and fairness principles. (2) to identify the environmental impact caused by implementing PPP defined in the Bolmong’s spatial plan. (3) to find out measures in mitigating  negative impacts resulting from PPP. The study was performed using quick appraisal approach by means of matrix analysis, expert judgements, secondary data, field survey, and literature. The result revealed that the score of PPP regarding linkage principle was very good (84.24%) as well as balance principle good (79.59%). The  fairness principle and SEA principle were  very good as well  which were  (83.72%),  (82.52%) respectively.  Identified nine issues of sustainable development resulted  negative and  positive impact . This study implied that mitigating  negative impacts could be achieved by integrating SEA principles to  articles that not fully considering SEA.